Comparative Analysis of Two Methodologies for Calculating Energy Performance and Energy Demand: a Case Study of the Municipal Office and Village Administration Building - Darmochwał-Podoba, Justyna; Rabczak, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In response to increasingly stringent European Union directives and national regulations on the energy performance of buildings, reliable and interpretable energy assessment methods are essential, particularly for public utility buildings due to their large floor areas and significant contribution to national energy demand. This study compares regulatory calculation results obtained for an administrative public utility building using two frameworks: the energy performance certificate (EPC) procedure and the energy audit methodology.
Keywords: building heat balance; energy demand; energy efficiency; Energy Performance Certificate; energy audit; Energy performance indicators